2019
DOI: 10.1002/celc.201801772
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Phase Cu3SnS4 Nanoparticles for Robust High Capacity Lithium‐Ion Battery Anodes

Abstract: With the evolution of Li-ion batteries, they have been employed in many applications. However, high energy density and power density batteries are yet to be developed to meet the necessities at the application end. Sulfides are a good choice as anode material as they show a much higher specific capacity than conventional graphite anodes. But unfortunately, sulfide dissolution and polysulfide shuttling are big drawbacks for their operation. Herein, single phase ternary metal sulfide Cu 3 SnS 4 (CTS) nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In the Nyquist plots of the Cu 2 SnS 3 electrodes at OCV (Fig. 7 a,b), a semicircle in the high-frequency region is attributed to the charge transfer resistance R ct and a straight sloping line in the low-frequency region is ascribed to Li + diffusion process in the bulk Zw [ 18 , 49 ]. The R ct of the annealed Cu 2 SnS 3 electrode is less than that of the as-prepared electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In the Nyquist plots of the Cu 2 SnS 3 electrodes at OCV (Fig. 7 a,b), a semicircle in the high-frequency region is attributed to the charge transfer resistance R ct and a straight sloping line in the low-frequency region is ascribed to Li + diffusion process in the bulk Zw [ 18 , 49 ]. The R ct of the annealed Cu 2 SnS 3 electrode is less than that of the as-prepared electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al synthesized this stoichiometric nanomaterial via one-pot solution processing method and tested the same for Liion battery anode (Figure 3a−c). 35 It delivered a high specific capacity of 1082 mAh g −1 at an applied current density of 0.2 A g −1 with an impressive cyclic stability of up to 950 cycles (Figure 3d,f). A specific capacity of 440 mAh g −1 at 3 A g −1 revealed that the system is capable of delivering high power (Figure 3e).…”
Section: Sulfides As Anode Materials For Li-ion Batterymentioning
confidence: 98%
“…It has been understood that the kinetic limitations posed by the initial conversion process have been the roadblocks to establishing the status of conversion-cum-alloying materials as an advancement over the simple alloying materials (Sn and Sb) from a commercial standpoint. , The extensively researched strategy employing the addition of conducting support though successful in enhancing the kinetics leads to a decline in the overall achievable capacity because of the overall inactivity or small contribution of conducting support toward Na + uptake. , Doping by some transition metals, Cu, Co, and Ni has been employed with only a little success for similar reasons. , …”
Section: Introductionmentioning
confidence: 99%
“…The advancement has been attributed to the buffering effect offered by the matrix of Na-chalcogenide/pnictide generated after the conversion process. , The past decade has witnessed an increased effort toward improving the electrochemical performance of Sn and Sb-based conversion-cum-alloying materials, via structural modifications, morphological modifications, or compositing strategies. Notably, structural modifications have involved self-assembly (1D van der Waals Sb 2 S 3 ), phase transitions (hexagonal-SnS 2 to orthorhombic-SnS), and metal doping (Cu 4 SnS 4 ; Sn 5 SbP 3 ). , Morphological modifications have encompassed thin sheets (ultrathin layered SnSe nanoplates; ultralong Sb 2 Se 3 nanowires) , and 3D morphologies (SnS bundles; SnS 3D flowers). , Compositing strategies have focused on compositing with modified carbon forms (in situ growth of Sb 2 S 3 on multiwalled carbon nanotubes; Sb 2 Se 3 nanodots in carbon-confined nanofibers; SnS confined in carbon nanospheres; Sb 2 Se 3 wrapped in reduced graphene oxide) and with structurally robust templating and supporting materials (core–shell–shell Sb 2 S 3 /Sb@TiO 2 nanorods) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation